Blood Pressure Parameters Among Smokers and Smokeless Tobacco Users in a Tertiary Level Hospital (Medicine Today, 2013)
This cross-sectional study was carried out to assess blood pressure parameters among adult male smokers and smokeless tobacco users. For this purpose, 105 male respondents were selected. They were divided into two groups; Group A-consisting of 30 were smokeless tobacco users and group B consisting of 75 smoker patients The participants were selected from medicine outdoor of Dhaka Medical College Hospital. In this study, the mean (±SD) of systolic blood pressure were 154.50±26.793 mm of Hg in Group A and 151.67±19.248 mm of Hg in group B respectively. Statistical analysis was done by unpairedt test, there were no statistical significant differences (P>0.05) of systolic blood pressure between Group A and Group B. The mean (±SD) of diastolic blood pressure were 96.67±10.933 mm of Hg in Group A and 86.47±14.745 mm of Hg in group B respectively. The mean (± SD) of diastolic blood pressure were significantly higher (P